A Review on Texture Descriptors in 2D Ear Recognition - R, Resmi K; Raju, G (International Journal of Computer Sciences and Engineering, 2025)
Ear recognition is an active area of research and automatic ear recognition is one of the challenging areas in biometric and forensic domains. Human ear contains large amount of unique features for recognition of an individual. There are different approaches and descriptors that achieve relatively good results in ear biometric recognition. Studies show that there is poor recognition performance in case of occlusion, illumination variation and pose variation. This paper presents an overview of different local texture descriptors in the field of automatic ear recognition. The local descriptors which calculate features from small local patches have proven to be more effective in real world situations compared to the global descriptors which extract features from whole image.